Teachers’ ability to use icebreaking activities in teaching speaking - Diana Fauzia Sari; Nini Darniati; Potjut Ernawati (Proceedings of AICS - Social Sciences, 2017)
The objectives of this study were to find out the teachers’ ability in implementing the icebreaking activities by the teachers in teaching speaking and to find out the problem are faced in implementing the icebreaking activities by the teachers of SMP Negeri 3 Banda Aceh. This research used descriptive qualitative method and the data were collected through observation checklist and questionnaire. The observation was taken from the teachers in order to know the teachers’ ability in implementing icebreaking activities in teaching speaking. Then, the questionnaire conducted to two English teachers who used the icebreaking in their teaching.The data collected were analyzed qualitatively. The researcher chose two English teachers in class VII and VIII, which are consist 30 students in each class and only focused on the teachers’ ability in implementing icebreaking activities in teaching speaking. The findings found that both teachers used a game as the type of icebreaking activities in speaking. The games were called “Paper Plane” and “Guess Your Animal”. The result of the study show that there were several problems faced by the teachers in implementing the icebreaking activities. The findings suggested for the teachers to have a good class management in the learning process and should be more focus on students’ participation. So the teachers do not have difficulty in handling the students while doing the icebreaking activity and the students also find no adversity in following the activity.